1983
DOI: 10.1177/000331978303400903
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease in Aortic Stenosis: Importance of Coronary Arteriography and Surgical Implications

Abstract: In our report, the presence or absence of angina pectoris did not predict the presence of coronary artery disease. A significant number of patients with aortic stenosis and angina pectoris have coronary artery disease but coronary artery disease also exists in asymptomatic form in a significant number of patients with severe aortic stenosis that could not be detected clinically and therefore suggests that the routine use of selective coronary arteriography is indicated in patients over 40 years undergoing card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…CAD was present in 61 % of the patients with an EA score 31 in the exercise test, and in 69% of the patients with EA score 3 2 . In the absence of angina in the history we have found CAD in 2 out of 12 patients (17%), contrary to reports by Basta et al Some authors have considered a history of EA to be sufficient to establish the diagnosis of coronary artery stenosis in patients with aortic stenosis (2), while others have argued that preoperative coronary angiography is necessary in all patients (7). We have found that EA recorded in the patient history has rather low diagnostic accuracy for coronary artery obstruction in patients with aortic stenosis.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…CAD was present in 61 % of the patients with an EA score 31 in the exercise test, and in 69% of the patients with EA score 3 2 . In the absence of angina in the history we have found CAD in 2 out of 12 patients (17%), contrary to reports by Basta et al Some authors have considered a history of EA to be sufficient to establish the diagnosis of coronary artery stenosis in patients with aortic stenosis (2), while others have argued that preoperative coronary angiography is necessary in all patients (7). We have found that EA recorded in the patient history has rather low diagnostic accuracy for coronary artery obstruction in patients with aortic stenosis.…”
Section: Discussioncontrasting
confidence: 94%
“…It is possible to evaluate the degree of arotic stenosis non-invasively by utilizing the Doppler technique to estimate the systolic pressure difference between the left ventricle and the aorta (1). The presence of coronary artery disease (CAD) in patients with aortic stenosis has been regarded as commonly associated with angina pectoris (2,3), but angina pectoris is also present in many cases of aortic stenosis without CAD (4-7) and CAD has also been found in the absence of angina pectoris (6,7). Therefore angina pectoris in the patient's history cannot be regarded as a reliable preoperative diagnostic indication of CAD (6,7,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that the incidence of coronary artery disease is more common in patients with aortic stenosis as compared to the general population. This phenomenon most likely reflects similar pathogenetic mechanisms related to calcific aortic stenosis and atherosclerotic coronary artery disease [26-28]. As the population ages, coronary artery disease and aortic stenosis will more often be seen in the same patient; in order to keep surgical mortality low, as it is reported in this study, a hybrid approach of surgical replacement of the aortic valve and percutaneous coronary intervention may need to be considered in selected patients.…”
Section: Discussionmentioning
confidence: 60%